Evaluation of mutual interaction

Leave a comment

We are going to evaluation the integral

\displaystyle G_{ij}^{hk} = \langle b_i(x) b_h(y) | \frac{1}{r_{xy}} | b_j(x) b_k(y) \rangle

Recalling the multi-pole expansion,

\displaystyle \frac{1}{r_{12}} = \sum_{l=0}^{\infty} \frac{4 \pi}{2l+1} \frac{r_{<}^l}{r_{>}^{l+1}} \sum_{m=-l}^{l} Y_{lm}^{*}(\Omega_1) Y_{lm}(\Omega_2)

and the basis

b_{nlm}(\vec{r}) = R_{nl}(r) Y_{lm}(\Omega)

Set an averaged basis

\displaystyle b_{nl}(\vec{r}) = R_{nl}(r) \frac{1}{\sqrt{2l+1}} \sum_{m=-1}^{l}Y_{lm}(\Omega)

\displaystyle \Gamma_{ij}^{hk}(l) = \frac{4 \pi}{2l+1}  \sum_{m=-l}^{l} \frac{1}{\sqrt{(2l_i+1)(2l_j+1)(2l_h+1)(2l_k+1)}} \\ \sum_{m_i,m_j}\int Y_{l_i m_i}^{*}(\Omega_1) Y_{l m}^{*}(\Omega_1) Y_{l_j m_j}(\Omega_1) d \Omega_1 \\ \sum_{m_h,m_k} \int Y_{l_h m_k}^{*}(\Omega_2) Y_{l m}(\Omega_2) Y_{l_k m_k}(\Omega_2) d \Omega_2

In the angular integrals, using Wigner 3-j symbol and the integral

\displaystyle\int Y_{l_1 m_1}(\Omega) Y_{l m}(\Omega) Y_{l_2 m_2}(\Omega) d \Omega \\= \frac{\sqrt{(2l_1+1)(2l+1)(2l_2+1)}}{\sqrt{4\pi}} \begin{pmatrix} l_1 & l & l_2 \\ 0 & 0 & 0 \end{pmatrix} \begin{pmatrix} l_1 & l & l_2 \\ m_1 & m & m_2 \end{pmatrix}

Y_{lm}^{*}(\Omega) = (-1)^m Y_{l(-m)}(\Omega)

\displaystyle \begin{pmatrix} l_1 & l & l_2 \\ m_1 & m & m_2 \end{pmatrix} = (-1)^{l_1+l+l_2} \begin{pmatrix} l_1 & l & l_2 \\ -m_1 & -m & -m_2 \end{pmatrix} \\ =(-1)^{l_1+l+l_2} \begin{pmatrix} l_1 & l_2 & l \\ m_1 & m_2 & m \end{pmatrix}

we have

\displaystyle\int Y_{l_i m_i}^{*}(\Omega) Y_{l m}^{*}(\Omega) Y_{l_j m_j}(\Omega) d \Omega \\= (-1)^{m_j} \frac{\sqrt{(2l_i+1)(2l+1)(2l_j+1)}}{\sqrt{4\pi}} \begin{pmatrix} l_i & l & l_j \\ 0 & 0 & 0 \end{pmatrix} \begin{pmatrix} l_i & l & l_j \\ m_i & m & -m_j \end{pmatrix}

\displaystyle\int Y_{l_h m_h}^{*}(\Omega) Y_{l m}(\Omega) Y_{l_k m_k}(\Omega) d \Omega \\= (-1)^{m_h} \frac{\sqrt{(2l_h+1)(2l+1)(2l_k+1)}}{\sqrt{4\pi}} \begin{pmatrix} l_h & l & l_k \\ 0 & 0 & 0 \end{pmatrix} \begin{pmatrix} l_h & l & l_k \\ -m_h & m & m_k \end{pmatrix}


\displaystyle \Gamma_{ij}^{hk}(l) = \sum_{m=-l}^{l} \sum_{m_i,m_j } (-1)^{m_j} \begin{pmatrix} l_i & l_j & l \\ 0 & 0 & 0 \end{pmatrix} \begin{pmatrix} l_i & l_j & l \\  m_i & -m_j & m \end{pmatrix} \\ \sum_{m_h,m_k} (-1)^{m_h} \begin{pmatrix} l_h & l_k & l \\ 0 & 0 & 0 \end{pmatrix} \begin{pmatrix} l_h & l_k & l \\  -m_h & m_k & m \end{pmatrix}

The 3-j symbol restricted that

l_i+l_j+l = even

l_h+l_k+l = even

m_i-m_j + m = 0,  |m_i| \leq l_i ,  |m_j| \leq l_j

-m_h + m_k +m = 0,  |m_h| \leq l_h ,  |m_k| \leq l_k

I guess it is the most simplified formula for the angular part.

The total integral is

\displaystyle G_{ij}^{hk} = \sum_{l=0}^\infty \Gamma_{ij}^{hk}(l) \langle R_i(x) R_h(y) | \frac{r_<^l}{r_>^{l+1}} |R_j(x) R_k(y) \rangle

The angular integral imposes condition for l .

I am not sure this is a correct way to treat the problem.

First, the averaged basis is still an energy eigen state. It is not the eigen state for the angular part. So, this averaging could introduces an error and we should reminded that this is an approximation. But in the perturbation view point, this averaged basis is still valid.

Second thing is, the sum

\displaystyle P_{(l_i m_i) (l_j m_j)}^{(l_h m_h)(l_k m_k)}(l) = \sum_{m=-l}^{l} \langle Y_{l_i m_i}|Y_{lm}^*|Y_{l_j m_j}\rangle \langle Y_{l_h m_h}|Y_{lm}|Y_{l_k m_k}\rangle

is not symmetry for exchange of i, j, h,k in general. For example,

\displaystyle \frac{-1}{3}=P_{(1-1) (00)}^{(11)(00)}(1) {\neq} P_{(00)(1-1)}^{(11)(00)}(1) = 0

This is a very uprising result that the mutual interaction dependent on the magnetic quantum number. Thus, in detail, we should use n l m m_s as a basis.

Third, the sum P_{ij}^{hk}(l) is depend on l . The mutual interaction require us to sum all possible l .

Fourth, the coupling between 1s2p triplet state, the total spin is S = 1, total L is L = 1, and the total angular momentum can be  J = 0, 1, 2 . In our treatment, we did not coupled the angular momentum in the calculation explicitly. In fact, in the integral of the spherical harmonic, the coordinate are integrated separately, and the coupling seem to be calculated implicitly. I am not sure how to couple two spherical harmonics with two coordinates.


Integration formulas of spherical harmonic

Leave a comment

There are several important and useful formulas for the integration of spherical harmonic. We simplify the notation,

\displaystyle \int_0^{\pi} \sin(\theta)d\theta\int_0^{2\pi}d\phi  = \int d\Omega

The first one is the average of spherical harmonic.

\displaystyle \int Y_{lm} d\Omega = \sqrt{4\pi} \delta_{l0}\delta_{m0}

The 2nd one is the orthonormal  condition.

\displaystyle \int Y^{*}_{l'm'}Y_{lm} d\Omega = \delta_{l'l}\delta_{m'm}

The 3rd one is triplet integral, we use the product of spherical harmonic,

\displaystyle \int Y_{l_1m_1}Y_{l_2m_2} Y^*_{l_3m_3} d\Omega \\ = \int \sum_{lm} \sqrt{\frac{(2l_1+1)(2l_2+1)}{4\pi(2l+1)}} C_{l_10l_20}^{l0} C_{l_1m_1l_2m_2}^{lm} Y_{lm} Y^*_{l_3m_3} d\Omega \\= \sqrt{\frac{(2l_1+1)(2l_2+1)}{4\pi(2l_3+1)}} C_{l_10l_20}^{l_30} C_{l_1m_1l_2m_2}^{l_3m_3}

The 4th one is another triple integral,

\displaystyle \int Y_{l_1m_1}Y_{l_2m_2} Y_{l_3m_3} d\Omega  \\ = \int \sum_{lm} \sqrt{\frac{(2l_1+1)(2l_2+1)}{4\pi(2l+1)}} C_{l_10l_20}^{l0} C_{l_1m_1l_2m_2}^{lm} Y_{lm} Y_{l_3m_3} d\Omega  \\ = \int \sum_{lmLM} \sqrt{\frac{(2l_1+1)(2l_2+1)}{4\pi(2l+1)}} C_{l_10l_20}^{l0} C_{l_1m_1l_2m_2}^{lm} \\ \sqrt{\frac{(2l+1)(2l_3+1)}{4\pi(2L+1)}} C_{l0l_30}^{L0} C_{lml_3m_3}^{LM}Y_{LM}d\Omega

\displaystyle = \sum_{lm} \sqrt{\frac{(2l_1+1)(2l_2+1)(2l_3+1)}{4\pi}} C_{l_10l_20}^{l0} C_{l_1m_1l_2m_2}^{lm} C_{l0l_30}^{00} C_{lml_3m_3}^{00}

Notice that

C_{lmLM}^{00} = (-1)^{L+M} \sqrt{\frac{1}{2L+1}} \delta_{Ll}\delta_{-m,M}

\displaystyle \int Y_{l_1m_1}Y_{l_2m_2} Y_{l_3m_3} d\Omega = \sqrt{\frac{(2l_1+1)(2l_2+1)}{4\pi (2l_3+1)}} C_{l_10l_20}^{l_30} C_{l_1m_1l_2m_2}^{l_3,-m_3} (-1)^{m_3}

using Wigner 3-j symbol,

C_{l_1m_1l_2m_2}^{l_3m_3} = (-1)^{l_1-l_2+m_3} \sqrt{2l_3+1} \begin{pmatrix} l_1 & l_2 & l_3 \\ m_1 & m_2 & -m_3 \end{pmatrix}

\displaystyle \int Y_{l_1m_1}Y_{l_2m_2} Y_{l_3m_3} d\Omega \\= \sqrt{\frac{(2l_1+1)(2l_2+1)(2l_3+1)}{4\pi}} \begin{pmatrix} l_1 & l_2 & l_3 \\ 0 & 0 & 0 \end{pmatrix} \begin{pmatrix} l_1 & l_2 & l_3 \\ m_1 & m_2 & m_3 \end{pmatrix} 

For other integral, we can use

Y^*_{lm}(\theta, \phi) = (-1)^{m}Y_{l(-m)}(\theta,\phi) = Y_{lm}(\theta, -\phi)